Vulnerability Assessment and Penetration Testing on Student Service Center System - Isnaini, Khairunnisak; Asyari, Muhammad Hasyim; Amrillah, Sigit Fathu; Suhartono, Didit (ILKOM Jurnal Ilmiah, 2024)
The number of system breaches has recently increased across various sectors, including the education sector. These breaches are carried out through various methods such as SQL Injection, XSS Attack, web defacement, malware, and others. Security vulnerabilities in the system also pose a potential threat to the Student Service Center owned by XYZ University, which stores a significant amount of confidential and sensitive data. The worst impact of all is the system is paralyzed, damaging the ongoing performance and reputation of institutions. The purpose of this research is to identify security vulnerabilities in the system using the Vulnerability Assessment and Penetration Testing (VAPT) method. The results showed that the system identified file upload functionality that poses a risk of being exploited for security attacks. Additionally, file path traversal can allow unauthorized access to directories, potentially enabling the injection of malicious code. Future research could explore the application of machine learning to enhance security measures and streamline the penetration testing process